ANALYSIS OF LANDSLIDES AND THE FORMATION OF WAY ELA NATUAL DAM, NEGERI LIMA, LEIHITU, CENTRAL MALUKU - Wisyanto Wisyanto; Heru Sri Naryanto (Jurnal Sains dan Teknologi Mitigasi Bencana, 2022)
The region of Indonesia is occupied by many volcanoes, both active and inactive. Volcanic products usually form a steep morphology and are often composed of volcanic deposits that are not yet compact or relatively loose. Such natural phenomena are very prone to landslides, and some of them forms natural dams that potential to be a source of flash floods. To find out the cause of the landslide, involving a big volume of landslide material and the formation of a natural dam, a study was conducted on the Way Ela Natural Dam. The research, in addition to using secondary data, also carried out field observations. The results showed that the landslide at Bukit Uluh Hatu involved a very large volume, due to the rock structure that was strongly fractured, the slope was very steep, the influence of the earthquake that enlarged opened layers and the high rainfall reached 360 mm. Meanwhile, the formation of natural dams is not only due to the large volume of landslides, but also due to the narrowing of the valleys which causes bottle necking of the flow of water and landslide material.